Screening for Cervical Pathologies in Antenatal Women Using Pap Smear at First Visit in a Tertiary Care Hospital: A Prospective Observational Study. - Farooqui, Uzma Amtul Shukoor; B. Sumalatha; Fatima, Bushra; Perum, Prithivi (Student’s Journal of Health Research Africa, 2025)
Background Cervical cancer remains one of the leading causes of morbidity and mortality among women in India. Despite the proven effectiveness of early detection through Pap smear screening, uptake remains limited, particularly during pregnancy a period that offers an ideal opportunity for screening and education. Objectives To assess the prevalence of cervical pathologies among antenatal women attending their first antenatal visit using Pap smear screening and to identify the frequency of pre-malignant and malignant cervical lesions. Methods This prospective observational study included 200 pregnant women attending their first antenatal visit at Niloufer Hospital, Hyderabad, between April 2021 and October 2022. After informed consent, Pap smears were collected and interpreted using the Bethesda 2001 classification. Demographic and obstetric profiles were recorded. Results The mean age was 26.05 ± 6.66 years; 69% were illiterate, and 57.5% were housewives. Pap smear findings revealed inflammatory smears in 37.5%, ASC-US in 10%, LSIL in 4%, and HSIL in 2.5%. Reactive cellular changes were noted in 8.5%, while 35% had normal cytology. The prevalence of pre-malignant lesions (LSIL and HSIL combined) was 6.5%. Only 3.5% of samples were unsatisfactory. Most participants were unaware of cervical screening and belonged to low socioeconomic backgrounds. Conclusion Pap smear screening during antenatal visits is both feasible and valuable for detecting cervical abnormalities in underserved populations. A notable prevalence of 6.5% pre-malignant lesions highlights the importance of early detection. Integrating Pap smear into routine antenatal care offers a strategic opportunity to improve awareness, initiate timely referrals, and reduce the burden of cervical cancer. Recommendations Integrate routine Pap smear screening into antenatal care to enhance early detection of cervical lesions, improve awareness, and ensure timely referrals, especially among underserved and low-literacy populations.